(untitled) (International Journal of Engineering and Computer Science, 2019)
This paper is aimed at development of a college database management system that can be used in any educational institution. Python flask framework is used to implement this application, that can be accessed throughout the institution or by any specific department of the institution. This system offers different features to the students and the members of the staff which includes attendance and marks of the students that can be accessed by both student and staff but can be only updated by staff of particular department . Students as well as staffs have separate logins that can be accessed by them easily . The system also includes a library management system which works in real time,a micro transport management system and a training and placement management system.Library management system keeps track of the books issued and also calculates the fine generated for delay in book returning and transport system maintains the record of each student i.e bus number ,route of that bus etc . A separate system for analysing the placement record of the college is also present . This system is developed to maintain and facilitate easy access to information to every member associated with this system. For this the users must be registered with the system after which they can access their accounts as well as modify data as per the permissions given to them. Python flask framework is the technology that we have used to develop the college management system. Flask is a web framework written in python. It can be classified into microframework because it does not require any particular tolls or libraries. However flask supports extension that can add application features . For frontend we have used HTML,CSS and javascript whereas for backend we have used python flask and mysql.This system helps college and universities to save time , money and resources.